Significantly enhanced electrocaloric effect by composition modulation in lead-free BaTiO3-based ceramics - Yingzhi Meng; Silin Tang; Zhaojie Wang; Xiang Niu; Hongfang Zhang; Dingyuan Wang; Yisong Bai; Biaolin Peng; Sheng-Guo Lu; Qingqing Ke; Laijun Liu (Journal of Materiomics)
The electrocaloric effect (ECE) offers a pathway to environmentally sustainable and easily miniaturized refrigeration technology, positioning it as a front-runner for the next generation of solid-state cooling solutions. This research unveils a remarkable ECE in a finely tuned (Ba0.86Ca0.14)0.98La0.02Ti0.92Sn0.08O3 ceramic, exhibiting a temperature shift (ΔT) of 1.6 K across more than 85% of the maximum ΔT (ΔTmax) and spanning an exceptionally wide operational range of 92 K. Our investigation on dielectric responses and ferroelectric polarization-electric field (P–E) loops suggests that the broad operational scope results from the fragmentation of extended ferroelectric domains into smaller domains and polar nano-regions (PNRs) supported by PFM analysis. Furthermore, the introduction of La enhances spontaneous polarization by significantly extending the maximum electric field that can be applied, facilitating high-performance ECE at ambient temperature. This study positions BaTiO3-based lead-free ceramic as a sustainable alternative for addressing the cooling demands of modern electronic components, marking a significant stride toward next-generation solid-state refrigeration.